Editorial: redrawing the boundaries for surgical intervention in hepatocellular carcinoma—authors' reply. Issue 5 (11th February 2019) - Wang, Yan‐Yan; Zhong, Jian‐Hong; Mao, Yi‐Lei; Li, Le‐Qun; Xing, Bao‐Cai
Abstract : Linked Content This article is linked to Wang et al and Liem and Janssen papers. To view these articles, visit https://doi.org/10.1111/apt.15074 and https://doi.org/10.1111/apt.15121 .